Methodological impact of starch determination on starch content and ileal digestibility of starch in grain legumes for growing pigs. Issue 1 (December 2017) - Jezierny, Dagmar; Mosenthin, Rainer; Sauer, Nadja; Schwadorf, Klaus; Rosenfelder-Kuon, Pia
Abstract Background Grain legumes represent a valuable energy source in pig diets due to their high starch content. The present study was conducted to determine the content and apparent ileal digestibility (AID) of starch in different grain legume cultivars for pigs by means of both a polarimetric and enzymatic method for starch determination. Methods Three experiments were conducted with six barrows each which were fitted with ileal T-cannulas. In total, 18 diets including six different cultivars of faba beans (Vicia faba L .) and peas (Pisum sativum L. ), five different cultivars of lupins (Lupinus luteus L., Lupinus angustifolius L. ), and one diet with a soybean meal (SBM) were fed. Results The starch content of faba beans and peas was greater (P < 0.05) when determined polarimetrically than enzymatically (438 vs. 345 g/kg dry matter (DM) in faba beans and 509 vs. 390 g/kg DM in peas, respectively). Considerable lower starch contents were obtained in lupins and SBM, with 82 and 48 g/kg DM (analyzed polarimetrically) and <1.1 and 3 g/kg DM (analyzed enzymatically), respectively. Mean values for contents of neutral detergent fiber (NDF) and acid detergent fiber (ADF) in grain legumes ranged from 111 and 79 g/kg DM in peas to 248 and 207 g/kg DM in lupins, respectively. Contents of condensed tannins in the colored flowered faba bean cultivars ranged from 2.1 to 7.4 g/kg DM. The AID of starch was greater (P < 0.05) in pea than in faba bean cultivars, and using the polarimetric starch determination method resulted in greater (P < 0.05) digestibility values than using enzymatic starch analysis (84 vs. 80% in faba beans and 86 vs. 83% in peas). Moreover, AID of starch differed (P < 0.05) within pea cultivars and starch digestibility in faba beans decreased linearly (P < 0.05) as the content of condensed tannins increased. However, there was no relationship between contents of NDF and ADF and AID of starch in pea and faba bean cultivars. Conclusion Both contents and AID of starch in grain legumes can vary as influenced by the analytical method used for starch determination. Generally, starch digestibility is greater when measured by polarimetric rather than enzymatic methods.